Hanguana thailandica (Hanguanaceae): a new peat swamp forest species from Thailand - Wijedasa, Lahiru S.; Niissalo, Matti A.; Chamchumroom, Voradol; Puudjaa, Pachok; Jumruschay, Thaveechock; Boyce, Peter C. (Phytotaxa, 2016)
A new species of Hanguana (Hanguanaceae), H. thailandica, is described and illustrated from Trang province, Peninsular Thailand. This is the second Hanguana species recorded in Thailand, along with the widespread helophytic H. malayana. The species is morphologically similar to Hanguana exultans and H. nitens found in swamp forests habitats in southern Peninsular Malaysia and Singapore. The conservation status of this species is accessed as Endangered according to the IUCN Red List Category and Criteria.